Spiritual Awareness and Academic Commitment in Islamic Religious Education Among Non-Religious University Students - Mokh. Iman Firmansyah; Agus Fakhruddin; Saepul Anwar; Qolbi Mujahidillah Adzimat Sukmayadi; Zalik Nuryana; Ahmad Hakam; Ach Fatayillah Mursyidi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Student engagement in compulsory Islamic Religious Education (IRE) has become an important concern in higher education, particularly among students enrolled in non-religious study programs who often perceive the course as peripheral to their disciplinary interests. Although previous research has examined Islamic education from curricular, pedagogical, and institutional perspectives, limited attention has been given to how spiritual awareness shapes students’ academic commitment through its interaction with self-efficacy and engagement. Consequently, this study explored these lived experiences using a qualitative phenomenological approach. Data were collected from 166 undergraduate students through open-ended questionnaires and complemented by semi-structured interviews with ten purposively selected participants. The data were analyzed using inductive thematic analysis. The findings indicate that spiritual awareness served as the primary motivational foundation for academic commitment by strengthening students’ perceptions of educational value, self-efficacy, and cognitive, affective, and behavioral engagement. Moreover, three patterns of academic commitment emerged: transformative commitment, strategic commitment, and instrumental compliance, reflecting varying degrees of integration between spiritual motivation and learning engagement. Overall, the findings demonstrate that meaningful participation in compulsory IRE is shaped by the dynamic interaction of spiritual, psychological, pedagogical, and social factors. Conceptually, this study advances scholarship on IRE by reconceptualizing academic commitment through an integrated framework that positions spiritual awareness as a central motivational resource for transformative learning.